Viabilidade técnica da utilização de fibra de curauá (Ananas erectifolius) como reforço em compósitos cimentícios laminados - Weber, Alessandra Monique (2018)
The aim of this search was to evaluate the technical viability of the use of curauá fiber (Ananas erectifolius) as reinforcement in laminated cementitious composites and to analyze the partial replacement of the cement with metakaolin. These composites constituted a cement matrix composed of CP V-ARI cement, sand, water and superplasticizer. The metakaolin was used to partially replace the cement in 50% aiming the consumption of the calcium hydroxide generated during the cement hydration. Previously the production of the composites was carried out analyzes of the properties of the curauá fiber and matrix dosage study. To evaluate the compatibility of the fiber with the matrix, tests were carried out to verify the inhibition index, evaluating whether the immersion in hot water of the fibers and the addition of the calcium chloride based additive influence the mixture. For the production of the laminated composites, the influence of the volumetric fraction of fibers in the composite (0%, 5%, 10%, 15% and 20%) and the replacement of the cement by metakaolin was investigated. The composite was produced with five layers, intercalating three layers of cementitious matrix and two layers of curauá fiber reinforcement. The tests aimed to evaluate the physical and mechanical behavior of the composites in different days of age (7, 28 and 90 days). The results indicate that the immersion of the fiber in hot water and addition of calcium chloride showed to be efficient to classify the vegetal fiber as of low inhibition with the matrix. For laminated composites, its production was considered technically feasible for additions in volume of curauá fiber up to 15%, because above this value the homogenization of the composite is impaired by the volume of fiber. In the long term, the addition of metakaolin as a substitute for cement increased by an average of 120% the mechanical properties of first crack stress of the composites and reduces the density between 8% and 12% The composites laminated with addition of curauá fiber presented physical-mechanical properties compatible with those of composites without reinforcement, being the curauá fiber as a reinforcement material in highstrength composites.